DIFFERENT APPROACH AND METHOD IN TEACHING ENGLISH DURING COVID-19 PANDEMIC - Liya Umaroh Liya Umaroh (ETERNAL (English Teaching Journal), 2021)
Learning is a series of complex and systematic activities. There was an interaction between teacher and students in classroom such as delivering material, learning certain subject, discussing for the topics, giving feedback, and becoming a great role model. Teaching and learning are two activities that occur simultaneously. When teaching English in classroom, teachers are adjusted as a center of learning process, they provide all facilities and play important role in classroom activities. Meanwhile conducting distance learning during this pandemic of Covid-19 is based on internet connection. Teachers are required to be literate in technology, moving from traditional teaching method to internet-based teaching method. This paper describes some approaches and methods in teaching English during Covid-19 Pandemic